An empirical study on the determinants of capital structure of Chinese Manufacturing listed companies - Yang, Jiayi (2017)
With the development of capital market, there has been more and more enterprises financing channels, the enterprises capital structure would also be adjusted. This shows that capital structure of the companies and the development of capital market are closely related. The number of listed companies in China's manufacturing companies takes up more than half of the total number of listed companies. This paper attempts to introduce the current situation of the capital structure of listed companies in Chinese manufacturing industry, as well as investigates the elements that affect the capital structure based on the firm level. Generally speaking, the conclusions obtained in this research are in line with previous studies. Growth opportunity, state ownership and firm size are positively connected with long-term leverage; liquidity and firm size have a positive relationship with short-term leverage; state ownership, liquidity and firm size are positively connected with total debt ratio. In contrast, manager shareholdings negatively relevant to long-term debt ratio; profitability as well as non-debt tax shields are inversely connected with short-term leverage and total leverage. This paper first introduces the background and characteristics of listed companies in Chinese manufacturing industry, then discusses the theories of capital structure. Moreover, it analyzes the influencing factors of the company level with the theories of capital structure. The study chooses manufacturing firms listed on the Shanghai stock exchanges from 2010-2014, using multiple linear regression methods to confirm that some firm-level factors have a considerable impact on capital structure. Finally, according to the empirical conclusion, the paper puts forward some limitations and provides several suggestions for optimizing the capital structure.